The value of ‘mega cohorts’ for psychiatric research: original investigation - Berger, Klaus; Rietschel, Marcella; Rujescu, Dan (The world journal of biological psychiatry, 2023)
Large population-based cohort studies offer the chance to assess a broad number of diseases and intermediate phenotypes and to estimate their frequencies in the general population. Because of their large sample size new symptom clusters and interactions of genetic, environmental and clinical factors in the onset and course of disease can be described. The German National Cohort (GNC) is one of the mega cohorts with a study-specific concept for the assessment of different psychiatric diseases and a focus on affective disorders and on emotional and cognitive functions. Aim of this manuscript is to describe different design approaches for a priorisation in the assessment of phenotypes for psychiatric and/or neurological disorders in large cohorts and to introduce the concept of studying emotional and cognitive functions and related disorders in GNC.